Análisis jurídico, doctrinario, comparado y de campo de la obligación legal de alimentos respecto de los hijos mayores de edad en la legislación ecuatoriana - Loaiza Romero, Julio Cesar (2014)
This thesis comprises a detailed study on the obligations of parents to the adult children, since the mere purpose of reaching the age of majority is no guarantee of economic independence thereof, as are immersed in their studies - completion of a university degree, master, preparation of oppositions, and other complementary training - oriented professional training , and living " to" and "from" parents , thus resulting in a disconnect between the age of majority and that they obtain what is called the doctrine and jurisprudence "economic majority." Regarding the legal food of adult children or emancipated , the social reality , according to which are to be interpreted legal standards, shows that children, even acquired the majority, remain under economic dependence parents, mainly for two reasons : first, because normally the academic formation of a minor, which is a condition for obtaining a job in a certain qualification element ends approximately between twenty and twenty-four, and second, the special difficulty which is currently accessing the labor market, a stable position and appropriate work in order to earn an income that allow you to live independently of their parents. In our society , where at age 21 had completed college career are minimal , there is a rate of 8 % unemployment, the jobs are scarce and require some specialization , which only provides the study and training. In our country, economic conditions at different times has given extreme situations that make varying job stability, professional, etc. , Of every citizen, among these parents that affected their income and standard of living permanently which implies that each project’s own life and that of their children, then inevitably vary according to the circumstances in which the country, and that should be taken into account, because it goes beyond the individual will, is the context socioeconomic determines the feasibility or otherwise of a law.